The Characteristic and Genesis of Volcanic Ash Soil in the North Slope Toposequence of Kawi Mountain in Malang Regency - A N Putra; S Sudarto; M L Rayes (Journal of Degraded and Mining Lands Management, 2015)
The volcanic ash soil in Kawi Mountain is composed by the amorphous materials consist of allophane, imogolite and ferrihydrite. Results of previous study showed that the phosphate retention in all soil profiles of northern slope toposequence of Kawimountain was less than 85%, yet the phosphate retention of volcanic ash soils is usually > 85 %. This raised a question that there is a different characteristics of soil in the northern slope tosequence of the Kawi Mountain compared to the other places. This research was conducted to study soil characteristics, mineral contents, and genesis processessoccuring in soil on the northern slope toposequence of Kawi Mountain. 5 pedons between high elevation and low elevation (P1, P2, P3, P4 and P5) to identified the soil characteristics. The Al, Fe, and Si extracted by acid oxalate, natrium pyrophosphate, and dithionite citrate to calculate the amorphous mineral content. The results show that. The results showed that there is a different in terms of the thickness of the A horizon, the C organic content and the soil acidity level that mainly found in P3 and P4 profiles. The most important soil genesis processess in the formation of the volcanic ash soils were likely clay illuviation (P5), melanization and braunification (P3), littering (P1) and the reduction of andic soil properties from the upper slope (P1 profile) up to the lower slope (P5 profile).